OPTIMIZING GRAPHIC ORGANIZERS TO IMPROVE STUDENTS’ READING COMPREHENSION (A Classroom Action Research at the Eleventh Year Students of SMA Negeri 6 Surakarta in 2009/2010 Academic Year) - Syaifudin Latif Darmawan (Premise: Journal of English Education and Applied Linguistics, 2012)
This action research is carried out to (1) identify whether graphic organizers can improve students’ reading comprehension; and (2) to describe the classroom situation when graphic organizers are employed in instructional process of reading comprehension.The research is conducted in two cycles from March to May 2010 in the second grade of SMA N.6 Surakarta. The procedure of the research consists of identifying the problem, planning the action, implementing the action, observing the action, and reflecting the result of the research. Qualitative data are collected through interview, observation, questionnaire, and research diary. Quantitative data are collected through test. To analyze qualitative data, the researcher used constant comparative method. It consists of four steps: (1) comparing incidents applicable to each category; (2) Integrating categories and their properties; (3) delimiting the theory; (4) Writing the theory. Meanwhile, to analyze quantitative data, the researcher employed descriptive statistic.   The result of the research shows that using graphic organizers can improve students’ reading comprehension and classroom situation. The improvement on students’ reading comprehension included; (a) students are able to find explicit information in a text; (b) students are able to comprehend of the text; (c) Students are able to find main idea in a paragraph; (d) students are able to infer the meaning of the text. The improvement of the classroom situation; (a) students come on time in the class (b) students are more motivated to join the class (c) Students pay more attention in the instructional process (d) students’ participation in responding the questions are high. In addition, the improvement also happens to the scores. The mean score increases from 57.56 in the pre-test, 63.34 in the formative test of cycle 1, and 69.56 in the post test of cycle 2. The mean score of writing is higher than the writing KKM (Kriteria Kelulusan Minimal) which is 63.  Based on the result of the research, it can be concluded that students’ reading comprehension could be improved by the implementation of graphic organizers. Therefore, it is recommended that (1) teacher should give the explicit model during implementing graphic organizers in teaching reading; and (2) teachers need to improve their acquisition of knowledge about graphic organizers through collaboration with other teachers.